Probing Surface Effects on α-NaYF4 Nanoparticles by Nuclear Magnetic Resonance - de Queiroz, Thiago B. (2020)
The structural properties of insulating α-NaYF4 (cubic) nanoparticles with size ranging within 4-25 nm were investigated by high-resolution 23Na and 19F solid-state nuclear magnetic resonance (NMR) spectroscopy under magic angle spinning (MAS) with single-pulse (SP-MAS), spin-echo (SE-MAS), inversion recovery, and 3Q-MAS experiments. The 23Na SP-MAS spectra show a broad peak around -18 ppm with a shoulder around -9 ppm, which becomes more prominent for the smallest nanoparticles. The 23Na nuclei resonating around -9 ppm demonstrate a longitudinal relaxation time of a few milliseconds, while the ones resonating around -18 ppm are on the order of 50-125 ms. This feature is noticed for all studied nanoparticles, but it is more evident for the smallest ones (φ ≲ 7 nm), especially among the batches with higher polydispersity. On the basis of these relaxation times, field-dependent measurements, and 23Na 3Q-MAS, we attributed the signal around -18 ppm to 23Na in the bulk of the nanoparticles and the signal around -9 ppm to surface or/and sites near defects, featuring higher fluctuations in the electric field gradient (EFG). The 23Na 3Q-MAS spectra provide evidence for two (and sometimes three) distinct Na sites in α-NaYF4 with similar quadrupole coupling but slightly different chemical shifts. The 19F SE-MAS spectra show a broad peak around -75 ppm with a small shoulder around -120 ppm corresponding to only ≈1% of the signal. The peak around -75 ppm is attributed to the stoichiometric NaYF4 composition, and its broadening is attributed to a distribution of Na- and Y-rich environments. The minor shoulder around -120 ppm is associated with the F-deficient NaYF4 structure. The 19F spin-spin relaxation time indicates some degree of mobility of the fluorine atoms, possibly due to the presence of F vacancies triggering hopping-like ion motion. The signal related to the F-deficient structure is greatly enhanced for the smallest nanoparticles (φ = 4 nm), i.e., along with the increase of 23Na surface effects and defects. Therefore, we correlate several NMR techniques to provide a fundamental structural view for nanoparticles used as upconversion host systems with prominent technological applications. Particularly for α-NaYF4, significant surface effects and defects must be expected for nanoparticles with dimensions in the order of few nanometers (φ ≲ 7 nm).